The Analysis of Water Sub Critical Hydrolysis Conditions on Content in Fatty Methyl Ester Biodiesel Production by Supercritical Methanol Method - Argo, Bambang Dwi; Swastomo, Budi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Biodiesel is an alternative fuel with a fatty acid ester composition made from raw vegetable oils/animal that has characteristics similar to diesel oil. High quality biodiesel fuel from oil/fat had been processed by two-stage supercritical metanol method which consisted of the hydrolysis process by mixing oil and water in sub-critical conditions that generated free fatty acids and glycerol, followed by esterification process that mixed free fatty acids with methanol in supercritical methanol conditions. Â In this research, hydrolysis of frying oil at sub-critical conditions had been conducted in various conditions. The conditions were the ration of oil to water and hydrolysis time in the reactor chamber at sub-critical condition. Materials used in this research were commercial frying cooking oil and bottled water. Â The purpose of this study was to find out the effect of hydrolysis at sub-critical condition on free fatty acids content generated in the production of biodiesel using super critical methanol. Â The results showed that there was an increasing percentage of ALB in the hydrolysis reaction with sub-critical water conditions. The highest and significant ALB was 67.10% that obtained in ratio of water to oil 25:75 and holding time of 20 minutes. Fatty acid produced in super-critical reactor was solid at room temperature and the behavior of this product still required a thermal analysis for designing exhausting pipe from the reactor in order to prevent blockage.Keywords: Biodiesel, hydrolysis, sub-critical, free fatty acids